Comparative analysis of authorship trends in the Journal of Hand Surgery European and American volumes: A bibliometric analysis. (July 2020) - Peters, Alexander W.; Savaglio, Michael K.; Gunderson, Zachary J.; Adam, Gremah; Milto, Anthony J.; Whipple, Elizabeth C.; Loder, Randall T.; Kacena, Melissa A.
Abstract: Background: The purpose of this study was to better understand the authorship publishing trends in the field of hand surgery. To accomplish this, a comparative analysis was completed between the European and American volumes of the Journal of Hand Surgery (JHSE and JHSA) over the past three decades. Well-established bibliometric methods were used to examine one representative year from each of the past three decades. The focus of the study was to examine changes in author gender over time as well as to compare authorship trends across the two volumes. Materials and methods: All JHSA and JHSE publications from 1985, 1995, 2005, and 2015 were placed into a Microsoft Excel spreadsheet. Data was collected for each publication including the gender of first and corresponding authors, corresponding author position, corresponding author country of origin, number of credited institutions, authors, printed pages, and references. Countries were grouped by regions. Results: A total of 450 and 763 manuscripts from JHSE and JHSA, respectively, met inclusion criteria. JHSE and JHSA both showed increases in most variables analyzed over time. Both journals showed an increase in female first and corresponding authors. JHSE and JHSA displayed a rise in collaboration between institutions and countries. Conclusions: Both JHSE and JHSA display increasing female inclusion in the hand surgery literature, which has traditionally been a male dominated field. The observed increase in collaboration between institutions and countries is likely linked to advances in technology that allow sharing of information more conveniently and reliably than was previously possible. As further advances are made socially and technologically, hopefully these trends will continue, leading to faster and higher quality research being generated in the field of hand surgery. Highlights: Orthopaedic hand literature has seen increases in collaboration over the past 30 years. Significant increase in female first authors in the orthopaedic hand literature. Female first and corresponding author manuscripts received the most citations.